PENGARUH JUMLAH PELARUT ETANOL DAN SUHU FRAKSINASI TERHADAP KARAKTERISTIK LEMAK KAKAO HASIL EKSTRAKSI NON ALKALIZED COCOA POWDER [The effect of amount of ethanol solvent and temperature fractionation on the characteristic of cocoa fat from the extracti - Carolina Maria Susanti; Ribut Sugiharto; Sri Setyani; Subeki Subeki (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Cocoa and its derivative products are examples of very potential  export comdities that could contributed to an increase in foreign exchange.  The extraction of non-alkalized cocoa powder resulted in pure cocoa extract as  the main product and cocoa fat as by product.  Cocoa fat can be exploited further to produce some final products, either food or non food products.    This research was aimed to study the effects of ethanol addition for extraction and fractionation temperature on the characteristic of cocoa fat.  This study used a Complete Randomized Block Design with two factor treatments and three replications.  The first factor was quantity of ethanol 450 ml, 600 ml, and 750 ml, and the second factor was temperature for fractionation 15oC, 18oC, and 21oC.  The data obtained were analyzed using Bartlett test for homogenity.  Tuckey Test was used for analyzing their additivity, then the data were analyzed using ANOVA to see differences among treatments.  The data were further  tested using Least Significant Difference at of 5%  level of significancy to find the best characteristic.  The results  showed that the best characteristic of cocoa fat obtained from the treatment of the addition of 750 ml ethanol and fractionation temperature 15oC.  It resulted in fat yield of 35.0382%, fat content of 86.742%, its flavor was close to characteristic of cocoa flavor ,and the composition of unsaturated fatty acids was 49, 71% of the total fatty acids. Keywords: cocoa fat, ethanol solvent, fractionation temperature